2015
DOI: 10.1007/s11250-015-0966-5
|View full text |Cite
|
Sign up to set email alerts
|

Faecal cortisol concentrations as indicator of stress during intensive fattening of beef cattle in a humid tropical environment

Abstract: The study evaluated the concentrations of faecal cortisol metabolites (FCM) in intensively fattened beef cattle from a feedlot in a humid tropical environment. A total of 360 bulls weighing 271-371 kg were kept confined in pens from the start to the end of the fattening period (FP). At 24 h after arriving at the feedlot, cattle were distributed into the pens according to their live weight: 271-320 kg, 321-370 kg, and >370 kg. At the start of the FP, four pens of each weight group were randomly selected, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Faecal glucocorticoid metabolites (FGMs) evaluation is gaining popularity as a non-invasive index of physiological stress in livestock animals [ 11 ]. It is the measurement of FGMs present in faeces collected from the animal, which reflects the amount of cortisol present in blood prior to excretion and the hypothalamo-pituitary-adrenal (HPA) axis activity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Faecal glucocorticoid metabolites (FGMs) evaluation is gaining popularity as a non-invasive index of physiological stress in livestock animals [ 11 ]. It is the measurement of FGMs present in faeces collected from the animal, which reflects the amount of cortisol present in blood prior to excretion and the hypothalamo-pituitary-adrenal (HPA) axis activity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in lactating cows, Ebinghaus et al [ 25 ] reported an FCM range of 9–48 ng/g on organic dairy farms, and Rouha-Mülleder et al [ 27 ] observed FCM concentrations at the farm level ranging from 9 to 48 ng/g. In beef bulls, Hernández-Cruz et al [ 28 ] showed slightly lower FCM concentrations of 8–18 ng/g during different stages of the fattening period. Conversely, Bertulat et al [ 29 ] showed FCM concentrations in lactating dairy cows ranging from 30 to 185 ng/g.…”
Section: Discussionmentioning
confidence: 99%
“…The range of glucocorticoid concentrations in bison bulls correlates with their hierarchy rank; bulls with high social status must pay the physiological price of high glucocorticoid levels ( 62 ). Furthermore, Tallo-Parra et al ( 64 ) measured fecal concentrations in Holstein cows ( Bos taurus ), while Hernandez-Cruz et al ( 63 ) measured fecal glucocorticoid concentrations in zebu bulls ( Bos indicus) of different ages from beef farms. Because of differences in species, design, and sex (males have higher cortisol levels), the studies cannot be directly compared.…”
Section: Fecal and Hair Glucocorticoids Concentrations In Free-rangin...mentioning
confidence: 99%